Analisis Pengetahuan Peternak dan Evaluasi Keberhasilan Program UPSUS SIWAB di Kecamatan Bayang, Kabupaten Pesisir Selatan - Tinda Afriani; Yurnalis Yurnalis; Firda Arlina; Dino Eka Putra (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2019)
UPSUS SIWAB Program is a Special Effort for Obligatory Bovine Cows which is a continuation of the government's program of self-sufficiency in meat. The purpose of this activity was to analyze breeders' knowledge and evaluate the success of the program in Bayang District, Pesisir Selatan Regency. The method used was a survey method with the results of direct interviews, and questionnaires with various community groups, and farmers. Data analysis used descriptive analysis. The result showed that the implementation of the UPSUS SIWAB program in 2018 in Bayang Subdistrict, Pesisir Selatan Regency has not been 100% implemented. However, the information of this special program was known by farmers, as much as 80% from the Animal Husbandry Department's counseling and 20% from fellow breeders. This shows that the counseling or socialization conducted by the government has not reached all farmers in Bayang District. Meanwhile, the results of the performance of this program were the number of acceptors who have been at IB in 2017 (1,213 individuals) and increased by 73% in 2018 (2,100 individuals). There were the number of Artificial Insemination in 2017 (1,314 times) and increased by 92% in 2018 (2,526 times), the number of acceptors pregnant in 2017 (1,158) and decreased by 2% in 2018 (1,136), the number of births in 2017 (766) and decreased by 80% in 2018 (151 tails).